THE DEVELOPMENT OF LEARNING MATERIALS IN INTERACTIVE E-BOOK SUBJECTS THE BASIC PROGRAMMING IN SMK TELKOM MAKASSAR - Alifya, Alifya (Department of Electrical Engineering, University of Patria Artha, 2018)
The purpose of this research is to know the Basic programming learning process that takes place before using the interactive E-book, knowing the process of developing learning materials interactive E-book, find out kevalidan, practicality, and the effectiveness of Interactive E-book developed. The research method used was Research and Development with the development model DDD-E consists of four phases, namely decide, design, develop, and evaluate. The results showed that the process of learning basic programming using learning materials based printed, educators have used LCD in the learning process to display a simulation programming, and overall the learners use personal laptops during the learning process takes place the initial stages of the development process is determining the objectives and the learning material, the next stages in designing competency map material, flowchart, interface, and stroryboard, continued with the process of making learning materials interactive E-book with 3D software, camtasia, PageFlip balabolka, ispring and adobe flash, the last stages evaluating learning materials is interactive E-book that has been developed is declared invalid by the validator expert content and media with very valid criteria, the average response of learners based on test performed very well, the mean response of educators against materials interactive E-book very good, the percentage of ketuntasan tests effective learners learning results, the average percentage of the observation activities of learners and educators in using learning materials interactive E-book is very active.